Is there any association between dietary inflammatory index and quality of life? A systematic review - Golmohammadi, Mona; Kheirouri, Sorayya; Ebrahimzadeh Attari, Vahideh; Moludi, Jalal; Sulistyowati, Reny; Nachvak, Seyed Mostafa; Mostafaei, Roghayeh; Mansordehghan, Maryam (Frontiers in Nutrition, 2022)
Background: The inflammatory potential of unhealthy diets can lead to the development of chronic diseases and also exacerbating their complications. Therefore, the present systematic review aimed to evaluate the association of dietary inflammatory index (DII) and quality of life (QOL) in human subjects. Methods: A systematic search was conducted in PubMed, Web of Science, and Scopus databases, using the combination of all search terms related to DII and QOL until May 2022. All eligible human studies published in English were included. Results: 327 studies were obtained from the first systematic search of the databases although, only 8 studies were eligible for the evaluation. Seven studies reported that there was a significant reverse association between DII scores and overall QOL and/or its subscales in different populations including patients with asthma, osteoarthritis, hemodialysis patients, multiple sclerosis, obese women, and also in healthy subjects. While, one study on postmenopausal women found no evidence of this association. Conclusion: This systematic review demonstrated that an anti-inflammatory diet might be associated with better QOL. However, future well designed clinical trials can provide better conclusions especially regarding the quantifying of this relationship.